2016
DOI: 10.17225/jhp00075
|View full text |Cite
|
Sign up to set email alerts
|

The impact on parents of having a child with haemophilia

Abstract: Wider access to modern treatment of haemophilia has led to a growing interest in the family’s role in management. An increasing amount of research has sought to understand the psychosocial impact of living with a child with haemophilia. Understanding how such demands affect parents and families who live with the daily threat of bleeding can help health professionals to provide effective support. A literature review was undertaken with the aim of summarising the key findings from studies published since 2000. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…46 Psychologists should support the families to address emotional and behavioural issues and anxieties, which might affect both delivery of prophylaxis and the family's quality of life. 47 Whether prophylaxis is administered through peripheral or central veins is dependent on the ease of venous access, the child and family. However, before inserting a CVAD, the risk of infection and thrombosis should be weighed against the relative ease of venous access.…”
Section: How To Start Prophylaxis In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Psychologists should support the families to address emotional and behavioural issues and anxieties, which might affect both delivery of prophylaxis and the family's quality of life. 47 Whether prophylaxis is administered through peripheral or central veins is dependent on the ease of venous access, the child and family. However, before inserting a CVAD, the risk of infection and thrombosis should be weighed against the relative ease of venous access.…”
Section: How To Start Prophylaxis In Childrenmentioning
confidence: 99%
“…Play therapy can be used to prepare, teach and distract the child, reducing difficulties around venous access 46 . Psychologists should support the families to address emotional and behavioural issues and anxieties, which might affect both delivery of prophylaxis and the family's quality of life 47 . Whether prophylaxis is administered through peripheral or central veins is dependent on the ease of venous access, the child and family.…”
Section: How To Start Prophylaxis In Childrenmentioning
confidence: 99%
“…The relationship between caregiver and the haemophilia centre plays an important role in their adjustment and improves their quality of life. 3 It was reported that haemophilia mothers' educational level was associated with general health and that parents' health was associated with coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Parents of children with coagulation factor deficiencies also experienced worries and stress as a result of these challenges 3 . Emotional and psychological effects of having a child with coagulation factor deficiencies are an important burden for parents/caregivers 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…28 Faktor emosi tidak hanya dirasakan oleh penyandang hemofilia namun juga orangtua. 29 Rasa bersalah yang dirasakan oleh ibu menjadi pembawa genetik bermanifestasi sebagai perlindungan berlebihan ibu terhadap anak hemofilia. Ketegangan emosi orangtua anak hemofilia lebih rendah dibandingkan orangtua anak penyakit kronik lain yang kurang bisa diobati.…”
Section: Menurut Konsensus Terbaru Scientific and Standardization Com...unclassified